1980
DOI: 10.1007/bf02407187
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and preliminary characterization of bone resorbing activity in freeze-dried gingiva of dogs

Abstract: The bone resorbing activity of suspensions or supernatants of freeze-dried powdered gingiva was studied by measuring the release of 45Ca from prelabeled fetal rat long bones in organ culture. Two preparations of noninflamed attached gingiva showed no bone resorbing activity, whereas all six preparations of inflamed marginal gingiva tested showed a dose-related stimulation of 45Ca release. Evidence of an osteoclastic mechanism was provided by the inhibition of the bone resorbing activity by calcitonin and corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…from our results the amount required might be very small. The interaction between endotoxin and other resorbers could also explain the results that we have obtained previously with freeze-dried gingiva (Hopps et al 1980). We found a significant correlation between the amount of PGE released and bone resorbing activity in supernatants of gingiva!…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…from our results the amount required might be very small. The interaction between endotoxin and other resorbers could also explain the results that we have obtained previously with freeze-dried gingiva (Hopps et al 1980). We found a significant correlation between the amount of PGE released and bone resorbing activity in supernatants of gingiva!…”
Section: Discussionsupporting
confidence: 83%
“…Prostaglandins have received the greatest attention, because PGE^ is found in inflamed gingiva (Goodson, Dewhirst & Brunetti 1974, Gomes et al 1976) and indomethacin, an inhibitor of prostagiandin synthesis, has been reported to reduce alveolar bone ioss in dogs (Nyman, Schroeder & Lindhe 1979). Using an in vitro organ culture assay, we found substantial bone resorbing activity in freeze-dried gingival powders obtained from dogs with chronic gingival inflammation (Hopps, Nuki &, Raisz 1980), The gingival extracts contained PGE, especially those with the greatest bone resorbing activity; however, the amount of PGE was far too small to be responsible for the entire bone resorptive response. One possible explanation for these results was that bone resorbing factors in the gingiva might interact to produce additive or synergistic responses.…”
Section: Introductionmentioning
confidence: 98%
“…We have found both high and low molecular weight bone-resorbing factors in extracts of gingiva from dogs with periodontal disease (Alander, Raisz, and Nuki, unpublished observation). The amount of prostaglandin present can not account for the resorptive response [17]. If low molecular weight peptidoglycans reach the bone, they could play a role in alveolar bone resorption.…”
Section: % Releasementioning
confidence: 99%
“…This activity was markedly reduced in clinically healthy gingiva (Soskolne et al 1980). and absent in oral mucosa (Hopps, Nuki &. Raisz 1980).…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have implicated prostaglandins as the resorbing factor (Goldhaber et al 1973, Gomes et al 1976 and higher levels of prostagiandin E2 (PGE2) have been shown to occur in inflamed gingival extracts than in healthy gingiva (Goodson, Dewhirst & Brunetti 1974, El Attar 1976. However, Hopps et al (1980) have suggested that the amount of PGE:^ in inflamed gingiva does not account for all the resorption stimulated by these extracts in an in vitro bone resorption assay. A role of bacterial products in resorption stimulated by these extracts has been suggested.…”
Section: Introductionmentioning
confidence: 99%